How Grade VIII Middle School Students Can Solve Problems Constructing Flat Sided Rooms with Polya Stages - Putri Andriani; William J. Fraser (HAMKA INSIGHT, 2023)
The purpose of this study was to determine the mathematical problem solving abilities of students with polya stages in solving problems related to flat sided geometric material. The method used in this type of research is descriptive qualitative. The population in this study were class VIII students of SMPIT Al Husna. Selection of samples with purposive sampling selected 6 people at high, medium and low levels. Data collection techniques in the form of tests, interviews and documentation. This study shows the results that in completing mathematical problem solving abilities to solve mathematical problems in the material of flat sided geometric shapes explain that the subject's answers vary greatly, at high, medium, low level subjects. Students with high mathematical ability (S1) did not make mistakes on the indicator aspect, students with medium mathematical ability (S2) made a few mistakes on the indicator aspect with the problem identification stage and students with low mathematical ability (S3) made mistakes on the indicator aspect with the completion stage problem and rechecking, it shows that S3 is more faculty.          Key words: problem solving ability, polya stages, flat side shapes.